Axillary Lymph Node Dissection Rates and Prognosis From Phase III Neoadjuvant Systemic Trial Comparing Neoadjuvant Chemotherapy With Neoadjuvant Endocrine Therapy in Pre-Menopausal Patients With Estrogen Receptor-Positive and HER2-Negative, Lymph Node-Positive Breast Cancer - Gwark, Sungchan; Noh, Woo Chul; Ahn, Sei Hyun; Lee, Eun Sook; Jung, Yongsik; Kim, Lee Su; Han, Wonshik; Nam, Seok Jin; Gong, Gyungyub; Kim, Seon-Ok; Kim, Hee Jeong (Frontiers in Oncology, 2021)
In this study, we aimed to evaluate axillary lymph node dissection (ALND) rates and prognosis in neoadjuvant chemotherapy (NCT) compare with neoadjuvant endocrine therapy (NET) in estrogen receptor-positive (ER+)/human epidermal growth factor receptor 2-negative (HER2-), lymph node (LN)-positive, premenopausal breast cancer patients (NCT01622361). The multicenter, phase 3, randomized clinical trial enrolled 187 women from July 5, 2012, to May 30, 2017. The patients were randomly assigned (1:1) to either 24 weeks of NCT including adriamycin plus cyclophosphamide followed by intravenous docetaxel, or NET involving goserelin acetate and daily tamoxifen. ALND was performed based on the surgeon’s decision. The primary endpoint was ALND rate and surgical outcome after preoperative treatment. The secondary endpoint was long-term survival. Among the 187 randomized patients, pre- and post-NST assessments were available for 170 patients. After NST, 49.4% of NCT patients and 55.4% of NET patients underwent mastectomy after treatment completion. The rate of ALND was significantly lower in the NCT group than in the NET group (55.2% vs. 69.9%, P=.046). Following surgery, the NET group showed a significantly higher mean number of removed LNs (14.96 vs. 11.74, P=.003) and positive LNs (4.84 vs. 2.92, P=.000) than the NCT group. The axillary pathologic complete response (pCR) rate was significantly higher in the NCT group (13.8% vs. 4.8%, P=.045) than in the NET group. During a median follow-up of 67.3 months, 19 patients in the NCT group and 12 patients in the NET group reported recurrence. The 5-year ARFS (97.5% vs. 100%, P=.077), DFS (77.2% vs. 84.8%, P=.166), and OS (97.5% vs. 94.7 %, P=.304) rates did not differ significantly between the groups. In conclusion, although survival did not differ significantly, more NCT patients might able to avoid ALND, with fewer LNs removed with lower LN positivity. Unique identifier: ClinicalTrials.Gov: NCT01622361. https://clinicaltrials.gov/ct2/show/NCT01622361